Wage inequality and skill supplies in a globalised world - Rotunno, Lorenzo; Wood, Adrian (Marseille, 2016)
"We investigate empirically how the relative wages of skilled and unskilled workers vary with their relative supplies in open economies. The investigation is based on a Heckscher-Ohlin model that is more general than the canonical version and related to recent advances in trade theory. Our results bridge the gap between trade economists and labour economists in views on the role of national labour markets in wage determination when countries trade. As labour economists believe, relative wages are sensitive to variation in skill supplies in open economies. As trade economists believe, however, this sensitivity decreases with openness to trade."